TINJAUAN PELAKSANAAN PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 MATA PELAJARAN PJOK PADA SISWA KELAS X IPA DI SMA NEGERI 4 PADANGSIDIMPUAN - Harahap, Adi Putra; Juita, Ardiah; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to determine the implementation of online learning during the COVID-19 pandemic on PJOK subjects in class X science students at SMA Negeri 4 Padangsidimpuan. The time of this research was carried out from September to November 2021. This type of research was descriptive with the number of samples in this study 160 people. This research instrument uses a questionnaire, to test the questionnaire with validity and reliability, then the data is analyzed by the percentage % formula to determine the amount of classification of data acquisition. From the results of data analysis on the implementation of online PJOK learning, 30 people were categorized as very good at 19.5%, then in the good category there were 124 people at 80.5%, and none were in the sufficient, less good, and very poor categories. From the results of the analysis of the research questionnaire data filled out by the principal, vice principal, and PJOK subject teachers in the implementation of online PJOK learning, 4 people are categorized as very good at 67%, then in the good category there are 2 people at 33%, and not some are in the category of sufficient, not good, and very poor.Key Words: Overview, Online Learning, PJOK